2005
DOI: 10.4049/jimmunol.174.1.110
|View full text |Cite
|
Sign up to set email alerts
|

2B4 (CD244) Is Expressed and Functional on Human Eosinophils

Abstract: Eosinophils are present in parasitic, allergic, various immunological, and malignant disorders as well as in a variety of idiopathic hypereosinophilic syndromes. However, their exact role in some of these conditions remains elusive. They can be activated both in vivo and in vitro by various agonists, such as Igs, lipid mediators, and cytokines. By phenotyping the surface of the eosinophils, it may be possible to better define their function(s) in different pathophysiological settings. In the present work we sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 55 publications
(65 reference statements)
6
75
1
Order By: Relevance
“…Indeed, we recently demonstrated that human eosinophils express gd TCR and showed its involvement in Colo-205 cell death induction (18). Another receptor shared between T cells and eosinophils, 2B4, a member of the CD2 family, has also been involved in the cytotoxic activity of eosinophils toward a B lymphoma cell line (21). However, in our study concerning a different target cell, the colorectal carcinoma cell line, 2B4 only played a minor role in tumoricidal activity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we recently demonstrated that human eosinophils express gd TCR and showed its involvement in Colo-205 cell death induction (18). Another receptor shared between T cells and eosinophils, 2B4, a member of the CD2 family, has also been involved in the cytotoxic activity of eosinophils toward a B lymphoma cell line (21). However, in our study concerning a different target cell, the colorectal carcinoma cell line, 2B4 only played a minor role in tumoricidal activity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil granule proteins that are released upon activation are known to be highly cytotoxic at least in vitro (15), but receptors triggering eosinophil degranulation and mediator release upon contact with tumor cells are unknown. So far, a single study demonstrated the cytotoxic activity of eosinophils toward a B lymphoma cell line in vitro and the implication of 2B4 receptor, a member of the CD2 family, in antitumor responses of eosinophils (21). In a recent study, we showed that eosinophils express the CD3-gdTCR, a receptor shared with the gd T cells (18).…”
mentioning
confidence: 99%
“…2B4 is expressed by all NK cells, as well as a subset of memory CD8 1 abT cells, gdT cells, basophils, monocytes and eosinophils [11][12][13][14][15]. 2B4 binds to the glycophosphoinositol anchored protein, CD48, expressed on all hematopoietic cells, with a similar affinity in mouse and human [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils were purified from peripheral blood of atopic asthmatics (see below) or age-and sex-matched normal individuals (blood eosinophil levels 5-10%) by MACS-negative immunomagnetic separation as described previously (10). Asthmatic donors were all atopic individuals (total IgE Ͼ100 IU/ml blood) requiring intermittent ␤ 2 -agonist treatment (forced expiratory volume 1 values ranging from 75-90% of normal).…”
Section: Human Peripheral Blood Eosinophil Donorsmentioning
confidence: 99%
“…These include CD2, CD48 (Blast-1 and BCM-1), CD58 (LFA-3), CD84 (Ly9B), CD150 (signaling lymphocytic activation molecule), CD229 (Ly9), 2B4 (CD244), BCM-like membrane protein, SF2001 (CD2F-10), NTB-A (SF2000 and Ly108), and CS1 (CD1-like receptor-activating cytotoxic effects) (9). We demonstrated that 2B4, the high-affinity ligand for CD48, activates human eosinophils to release IL-4 and IFN-␥, and to develop cytotoxic activity against tumor cell lines in vitro (10). Inasmuch as eosinophils express both CD48 and 2B4, we have focused our current study on CD48.…”
mentioning
confidence: 99%